2017
DOI: 10.1111/eos.12339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ISO 4049: water sorption and water solubility of resin cements

Abstract: The aim of this study was to evaluate the water sorption and solubility test design of ISO 4049 for resin cements. Sorption and solubility of six dual-curing resin cements [RelyX Unicem 2 Automix (RUN), Multilink Speed CEM (MLS), Panavia SA Plus (PSA), RelyX Ultimate (RUL), Multilink Automix (MLA), and Panavia V5 (PV5)] were analyzed by storage in distilled water after dual-curing. In addition, sorption and solubility during thermal cycling were assessed with self-cured and dual-cured specimens. After water st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 42 publications
1
48
0
7
Order By: Relevance
“…The present study is the first reporting the bonding effectiveness between PV5 and Y-TZP ceramic after NTP treatment. Although luting resins containing 10-MDP have demonstrated good bonding performance in vitro studies [34,40,41], studies demonstrated that this monomer appeared hydrolytically unstable in water [42], and an acidic monomer causes a low degree of conversion and weak bonding compared to Panavia V5, which does not contain 10-MDP in the cement [28]. Analysis of fractured interfacial zone shows a predominance of mixed failures for all experimental groups, which might be related to efficient bond strength.…”
Section: Discussionmentioning
confidence: 90%
“…The present study is the first reporting the bonding effectiveness between PV5 and Y-TZP ceramic after NTP treatment. Although luting resins containing 10-MDP have demonstrated good bonding performance in vitro studies [34,40,41], studies demonstrated that this monomer appeared hydrolytically unstable in water [42], and an acidic monomer causes a low degree of conversion and weak bonding compared to Panavia V5, which does not contain 10-MDP in the cement [28]. Analysis of fractured interfacial zone shows a predominance of mixed failures for all experimental groups, which might be related to efficient bond strength.…”
Section: Discussionmentioning
confidence: 90%
“…For RUN results were inverse, which might be explained by a higher amount of unreacted phosphoric acid ester groups, resulting in a higher degree of water up-take and thus an increased CS. Higher sorption was previously recorded for RUN for autopolymerized specimens [ 9 ]. Aging of autopolymerized specimens significantly decreased CS for MLA and PV5 due to a degradation of the material that might be due to a lower degree of polymerization than for the light-cured specimens.…”
Section: Discussionmentioning
confidence: 87%
“…Values of RUN and RUL were increased after aging. RUL and RUN previously presented high sorption that might have been responsible for increasing their strength after thermal cycling [ 9 ]. Light-cured specimens correlated linearly before and after aging and were therefore less susceptible to aging than autoplymerized specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ich zaletą jest uproszczona procedura kliniczna oraz skrócenie czasu zabiegu. 15 Chociaż potencjał adhezyjny cementów żywicznych wraz z hydrofilowością i sorpcją są krytycznymi parametrami, i większość badań skupia się właśnie na nich, 8,[15][16][17] to również właściwości mechaniczne są ważne dla klinicznej trwałości uzupełnienia protetycznego.…”
Section: Dyskusjaunclassified